Evaluation of Potency and Duration of Immunity Elicited by a Multivalent FMD Vaccine for Use in South Africa - Peta, Faith R. M.; Sirdar, M. M.; van Bavel, Peter; Mutowembwa, P. B.; Visser, N.; Olowoyo, J.; Seheri, M.; Heath, Livio (Frontiers in Veterinary Science, 2021)
South Africa experiences sporadic foot and mouth disease (FMD) outbreaks irrespective of routine prophylactic vaccinations of cattle using imported commercial vaccines. The problem could be mitigated by preparation of vaccines from local virus strains related to those circulating in the endemically infected buffalo populations in the Kruger National Park. This study demonstrates the individual number of protective dose of five vaccine candidate strains after homologous virus challenge, as well as the vaccines safety and onset of humoral immunity in naïve cattle. Furthermore, the duration of post vaccination immunity over 12 months period is shown, when a multivalent vaccine prepared from the five strains is administered as a primary dose with or without booster vaccinations. The five monovalent vaccines were shown to contain a 50 % protective dose between four and 32, elicit humoral immunity with antibody titers ≥ 2.0 log10, from day seven post vaccination and cause no adverse reactions. Meanwhile, the multivalent vaccine elicited antibody titers ≥ 2.0 log10 and clinical protection up to 12 months when one or two booster vaccinations were administered within 6 months of the primary vaccination. An insignificant difference between the application of one or two booster vaccinations was revealed. Owing to the number protective dose, we anticipate that the multivalent vaccine could be used successfully for prophylactic and emergency vaccinations without adjustment of the antigen payloads. Furthermore, a prophylactic vaccination regimen comprising primary vaccination of naïve cattle followed by two booster vaccinations 1.5 and 6 months later, could potentially maintain herd immunity over a period of 12 months.